2016
DOI: 10.1111/crj.12493
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overlap syndrome in chronic obstructive pulmonary disease patients without sleep apnea symptoms

Abstract: Background The co‐existence of chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) is a common phenomenon referred to as overlap syndrome (OS). In this study, we evaluated the prevalence of OS in mild hypoxemic COPD patients without OSA symptoms and compared characteristics of OS and COPD patients. Methods Forty‐five COPD patients (mean FEV1 1671.3 ± 532.0 mL) with mild hypoxemia presenting no sleep apnea symptoms (96% men, mean age 67.7 ± 8.5 years) were involved in this study. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
(21 reference statements)
3
12
0
3
Order By: Relevance
“…On the other hand, more than half (52.9%) of the patients reported daytime sleepiness as a symptom and this rate was significantly higher in patients with OSA. It is known that ESS appropriateness is controversial in COPD despite it was commonly used for sleep apnea in the literature . Consistent with this statement, no correlation was found between ESS and polygraphic parameters in this study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…On the other hand, more than half (52.9%) of the patients reported daytime sleepiness as a symptom and this rate was significantly higher in patients with OSA. It is known that ESS appropriateness is controversial in COPD despite it was commonly used for sleep apnea in the literature . Consistent with this statement, no correlation was found between ESS and polygraphic parameters in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Probable etiologies of sleep disorder in patients with COPD are investigated and their relationship with objective sleep parameters is examined. A common outcome of most of the studies is that sleep disturbance was found in patients with COPD but it was not correlated with objective nocturnal parameters . Similar to these studies, there were no correlations between polygraphic measures and sleep quality, daytime sleepiness and QoL in this study.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…First, these overlaps are frequently unrecognized. Patients with asthma/COPD may not report sleep symptoms, 72 or may attribute them to the primary lung disease. Standard screening questionnaires are also imperfect.…”
Section: Where Next?mentioning
confidence: 99%
“…Сидром обструктивного апноэ сна широко распространен среди больных хронической обструктивной болезнью легких (ХОБЛ), достигая, по оценкам ряда авторов, от 10 % до 66 % и ассоциируясь с увеличением индекса массы тела, степени тяжести бронхиальной обструкции [1,2,3,4].Современные исследования показывают, что синдром обструктивного апноэ сна у больных ХОБЛ ассоциируется не только с нарушениями сна и бодрствования, но и с повышенными риска-ми обострений ХОБЛ, госпитализаций, смерти от всех причин [1,3,5,6,7,8]. Среди возможных механизмов неблагоприятных исходов при сочетании этих заболеваний обращается внимание на персистирующее системное воспаление [2,4,8,9]. Персистирующее системное воспаление у больных ХОБЛ ассоциируется не только с повышенными рисками обострений, но и с неблагоприятными исходами ряда экстрапульмональных заболеваний и смерти от всех причин, находящимися в слабой взаимосвязи со степенью функциональ-ных и структурных изменений легких.…”
Section: Introductionunclassified